Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz a) (2 1/4)^(-1)+3^(-2) b) 4,5^(-2)-3^(-4)4.78 gwiazdek na podstawie 9 opinii

Oblicz a) (2 1/4)^(-1)+3^(-2) b) 4,5^(-2)-3^(-4)

5Zadanie
1Zadanie
2Zadanie
3Zadanie
4Zadanie
5Zadanie

`a) \ \ (2 1/4)^(-1)+3^(-2)=(9/4)^(-1)+(1/3)^2=4/9+1/9=5/9` 

`b) \ \ 4,5^(-2)-3^(-4)=(4 1/2)^(-2)-(1/3)^4=(9/2)^(-2)-1/81=(2/9)^2-1/81=4/81-1/81=3/81=1/27` 

`c) \ \ (1/2)^(-6)+(1/4)^(-3)+(1/8)^(-2)+(1/64)^(-1)=2^6+4^3+8^2+64=` 

`=64+64+64+64=256`